2015
DOI: 10.1093/schbul/sbv058
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Effectiveness of a Multi-Element Psychosocial Intervention for First-Episode Psychosis: Results From the Cluster-Randomized Controlled GET UP PIANO Trial in a Catchment Area of 10 Million Inhabitants

Abstract: Integrated multi-element psychosocial interventions have been suggested to improve the outcomes of first-episode psychosis (FEP) patients, but they have been studied primarily in experimental settings and in nonepidemiologically representative samples. Thus, we performed a cluster-randomized controlled trial, comparing an integrated multi-element psychosocial intervention, comprising cognitive behavioral therapy, family intervention, and case management, with treatment as usual (TAU) for FEP patients in 117 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
81
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 60 publications
5
81
0
1
Order By: Relevance
“…47 A better understanding of the developmental antecedents of psychosis may lead to both early identification and novel targeted interventions. 810 …”
Section: Introductionmentioning
confidence: 99%
“…47 A better understanding of the developmental antecedents of psychosis may lead to both early identification and novel targeted interventions. 810 …”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that early intervention for psychotic disorders such as schizophrenia can improve outcomes, [1][2][3][4][5] and 2 cluster randomized trials 6,7 have demonstrated effectiveness in routine service settings. One unanswered question is whether the increased costs of comprehensive first episode psychosis (FEP) programs are offset by reduced inpatient costs, or whether the value of health benefits justifies the additional costs.…”
Section: Introductionmentioning
confidence: 99%
“…We determined that there was sufficient evidence to develop a scale that is based on the evidence for the effectiveness of individual components of FEPS and on evidence from robust large-scale randomized controlled trials of the effectiveness of FEPS (9)(10)(11)(12). In contrast to a scale developed from a single effective program, a scale that is derived from a comprehensive review of the literature can be more easily applied to a broad range of programs.…”
mentioning
confidence: 99%